Design and Construction of Screened Wells for Agricultural Irrigation Systems - Brian Boman; Sanjay Shukla; J. D. Hardin (EDIS)
Circular 1454, a 12-page illustrated publication, describes the proper design of screened wells to ensure compatibility with the rest of the irrigation system and long life, efficiency, and economic operation. Published by the UF Department of Agricultural and Biological Engineering, October 2006.